Path-Goal Leadership Style and Its Relationship with Nurse Motivation and Performance: A Cross-Sectional Study - Batewa, Erny; Ellina, Agusta Dian; Peristiowati, Yuly (Lembaga Chakra Brahmanda Lentera (Chakra Brahmanda Lentera Institute) [CANDLE], 2025)
Background: Nursing services aim to provide optimal care through effective planning, organization, and employee management. Nurses play a key role in health services at hospitals, health centers, and other facilities. Objective: The study analyzed the relationship between the leadership of the head of the family and the work motivation and performance of nurses, based on the Path-goal theory, at the Regional General Hospital of Banggai Regency. Methods: This study employed an observational-analytic design with a cross-sectional approach, involving 146 inpatient nurses. A simple random sampling technique was used to recruit participants. Inclusion criteria included nurses working in inpatient units for at least 6 months and willing to participate, whereas nurses currently on leave, in training, or assigned to non-clinical administration were excluded. The independent variable was the head nurse's leadership style, while the dependent variables were nurse motivation and performance. Data collection and reporting followed the STROBE (Strengthening the Reporting of Observational Studies in Epidemiology) guideline. Data were analyzed using the Spearman rho test with a significance level of α = 0.05 Result: The results showed that directive leadership was not associated with nurse motivation (p = 0.570) or performance (p = 0.257). However, supportive leadership significantly influenced motivation (p < 0.001) and performance (p = 0.049). Participative leadership also demonstrated a positive effect on motivation (p < 0.001) and performance (p = 0.035). Similarly, achievement-oriented leadership was associated with higher motivation (p < 0.001) and better performance (p = 0.031). Conclusion: In conclusion, directive leadership does not affect the motivation or performance of nurses at Banggai District Hospital. Conversely, supportive, participative, and achievement-oriented leadership significantly enhances both motivation and performance.